Correlation between Hospital Image and Patient Satisfaction toward Loyalty in Hospital: A Scoping Review - Gabrina Selvi Yanuarista; Septo Pawelas Arso; Sri Winarni (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2025)
Introduction: The Indonesian healthcare sector has grown quite impressively these years, with increased competition due to private investments and rapid development in the services of hospitals. Even though government hospitals dominate the market with 51.4%, the business environment is promising, with private hospitals having a low concentration ratio that demands strategic initiatives in terms of service quality and reputation. This research investigates the relationships between hospital image, patient satisfaction, and loyalty. Methods: This scoping review utilized databases like Google Scholar, PubMed, and Science Direct, focusing on studies published between 2019 and 2024. The keywords used for this scoping review were: (Hospital Brand OR Hospital Image OR Hospital Reputation OR Hospital Identity OR Hospital Branding Identity OR Hospital Branding) AND (Patient Satisfaction OR Satisfied Patient OR Healthcare Satisfaction OR Patient Experience OR Hospital OR Healthcare Service Evaluation OR Patient Perception of Care OR Patient Perception of Service) AND (Patient Loyalty OR Patient Retention OR Patient Adherence OR Patient Commitment OR Hospital Loyalty OR Healthcare Consumer Retention OR Healthcare Consumer Loyalty). Results: After screening 367 records, 101 studies were assessed for eligibility, and 12 met the inclusion criteria. Results consistently highlight the direct and indirect impact of hospital reputation on patient satisfaction and loyalty. Conclusion: Patient satisfaction played a major role in forming patient loyalty. Healthcare providers should be more aware of developing services through medical equipment and medical personnel recruitment, which may lead to the improvement of patient experiences and create satisfaction and loyalty. Future research needs to investigate complex correlations that may form patient loyalty in a hospital setting including socio-economic aspects, perceived value, and service quality.